Equitable and Inclusive Landscape Restoration Planning: Learning from a Restoration Opportunity Assessment in India - Singh, R.; Shelar, K.; Duraisami, M.; Anderson, W.; Gautam, R.S. (University of Wisconsin Press, 2021)
Local people must be at the center of restoring landscapes. This paper adapts the popular Restoration Opportunity Assessment Methodology (ROAM), which helps show where land can be restored in a given area by growing trees or protecting forests, to the economically poor yet resource-rich Sidhi District of Madhya Pradesh in India. By employing an intersectional adaptive governance lens and including the perspectives of people and organizations throughout the larger social landscape, we analyzed the multiple benefits landscape restoration can have on ecosystem services, social inclusion, the economy, and local livelihoods. These participatory methods and tools draw attention to the critical socio-economic components of restoration. The findings indicate that different social groups, like powerful men and marginalized women, have different restoration goals (even for tree species selection). They also show that investing in restoration can create thousands of jobs and secure thousands of rural livelihoods. Analyses that produce these socioeconomic insights can inform implementation strategies that are both inclusive and actionable on the ground. They can also identify roadblocks, like unclear land tenure and resource rights, which can impede restoration. Most importantly, these inclusive strategies can ensure that local people serve as more than passive beneficiaries. They place them in their appropriate role as the central stakeholders driving implementation.